Driving restrictions following defibrillator implantation significantly affect recipients' ability to maintain employment. (3rd October 2022) - Bjerre, J; Hansen, M H; Schou, M; Rasmussen, T B; Ruwald, A C
Abstract: Background: Following defibrillator implantation or in case of ICD therapy, ICD recipients are subject to temporary driving restrictions for private driving. Moreover, the current European recommendations permanently ban professional driving which can significantly alter the recipients' daily life and ability to maintain employment. Aim and methods: To investigate Danish ICD recipients' perspective on driving restrictions following ICD implantation we distributed a questionnaire to all living ICD patients with a first-time implantation between 2013 and 2016 (n=3913). We linked questionnaire responses with relevant nationwide Danish registers. Results: Among the 2741 ICD recipients who responded to the questionnaire (response rate 71%, 47% primary prevention, 83% male, median age 67 years), 2513 (92%) held a valid private driver's license at time of implantation and 175 (7%) were actively using a professional driver's license. Almost all (n=2344, 94%) had resumed driving following device implantation. Among those with a driving ban of at least 1 month following either ICD implantation or ICD therapy (n=911), 26% stated the restrictions had severely impeded their daily life, significantly more in the professional drivers group compared with the private drivers (32% vs 24%, p=0.01). Including only patients working prior to implantation (n=465), 27% stated they were very limited and 20% somewhat limited in maintaining employment following implantation due to the driving restrictions. Likewise, 23% were very limited and 19% somewhat limited in getting to their job. Among the active professional drivers (n=175), 58 (33%) stated they had lost their job as a direct consequence of the post-implantation driving restrictions. Conclusion: Every fourth Danish ICD recipient is severely limited in their daily life due to the driving restrictions. Both professional and private drivers are significantly affected with regards to maintaining employment following implantation, which should be a key focus in rehabilitation programs. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): The Danish Heart Foundation and Arvid Nilssons Fond